Answer: -1 and 5.
Step-by-step explanation:
x - 4x = 5 : Move the constant to the left.
x^2 - 4x - 5 = 0 : Rewrite the expression.
x^2 + x - 5x - 5 = 0 : Factor the expressions.
x(x+1) - 5(x+1) = 0 : Factor the expression.
(x+1)(x-5) = 0 : Seperate into possible cases.
x + 1 = 0, x - 5 = 0 : Solve the equations.
x = -1, x = 5 : The equation has 2 solutions.
Answer:
k = 4
Step-by-step explanation:
if f(x) is divided by (x - h) then f(h) is the remainder
f(x) = 2x³ - 3x² + kx - 1
divided by (x - 1) , so h = 1 , then
2(1)³ - 3(1)² + k(1) - 1 = 2
2 - 3 + k - 1 = 2
- 2 + k = 2 ( add 2 to both sides )
k = 4
Answer:
88 won and 66 lost
Step-by-step explanation:
Won =
×4 = 88 games
Lost = 154 - 88 = 66 games
Answer:
question 7 is A
Step-by-step explanation:
(10 + 9) x (3 - 1) x 2 = +75
19 x 2 x 2
76
76 > 75